Heterobeltiosis and combining ability among Egyptian cotton genotypes under well irrigated and water deficit conditions - Abdel-Moneam, Maamoun A.; Ghoneima, Mohammed H.; Abido, Waleed A. E.; Hadházy, Ágnes; El-Mansy, Yaser M.; El-Shazly, Mohab W. (Acta Agraria Debreceniensis, 2020)
Two field experiments were carried out during the 2014 and 2015 seasons to evaluate certain genotypes of Egyptian cotton under well irrigated and water stress conditions. The cross combination Giza 69 x Australy recorded the best values for better parent heterosis for all physiological measurements and earliness index under well irrigated and deficit conditions. Of the female parents, Giza 86 was found to be a good general combiner for most yield characters under both normal and stress conditions, followed by Giza 94. Data illustrated that Giza 45 was the best general combiner for most fiber quality traits under both conditions. The cross combinations Giza 86 x Dandra and Giza 69 x Pima S6 showed significant positive SCA values for seed cotton and lint yield/plant under well irrigated and water deficit conditions. However, the combinations Giza 77 x PimaS6 and Giza 94 x 10229 recorded significant positive SCA effects for seed cotton yield/plant under stress. Whilst, the cross Giza 68 x 10229 recorded significant desirable SCA effects for most fiber quality properties. In this context, the estimates significant positive general and specific combining ability effects indicated that the epistasis and/or dominance effects for F1 hybrid in cotton could be important to a certain extent.